Investigation of green synchronous spectrofluorimetric approach for facile sensitive estimation of two co-administered anti-cancer drugs; curcumin and doxorubicin in their laboratory-prepared mixtures, human plasma, and urine - Diaa Dagher; Heba Elmansi; Jenny Jeehan Nasr; Nahed El-Enany (BMC Chemistry, 2024)
Abstract Recently, phytochemicals play an important role in cancer management. Curcumin (CUR), a natural phytochemical, has been co-administered with widespread chemotherapeutic agents such as doxorubicin (DOX) due to its excellent antitumor activity and the ability to lower the adverse reactions and drug resistance cells associated with DOX use. The present study aims to determine DOX and CUR utilizing a label-free, selective, sensitive, and precise synchronous spectrofluorimetric method. The obvious overlap between the emission spectra of DOX and CUR prevents simultaneous estimation of both analytes by conventional spectrofluorimetry. To solve such a problem, synchronous spectrofluorimetric measurements were recorded at Δλ = 20 nm, utilizing ethanol as a diluting solvent. Curcumin was recorded at 442.5 nm, whereas DOX was estimated at 571.5 nm, each at the zero-crossing point of the other one. The developed method exhibited linearity over a concentration range of 0.04–0.40 μg/mL for CUR and 0.05–0.50 μg/mL for DOX, respectively. The values of limit of detection (LOD) were 0.009 and 0.012 µg/mL, while the values of limit of quantitation (LOQ) were 0.028 and 0.037 µg/mL for CUR and DOX, respectively. The adopted approach was carefully validated according to the guidelines of ICH Q2R1. The method was utilized to estimate CUR and DOX in laboratory-prepared mixtures and human biological matrices. It showed a high percentage of recoveries with minimal RSD values. Additionally, three different tools were utilized to evaluate the greenness of the proposed approach.